Formulation and Evaluation of Nanoemulsion Kelakai (Stenochlaena palustris) Herbs with Composition of Smix (Tween 80 and Glycerin) and Pine Oil - Helsawati, Helsawati; Ratnapuri, Prima Happy; Fitriana, Mia (Borneo Journal of Pharmacy, 2023)
Kelakai (Stenochlaena palustris) herb is a typical South Kalimantan plant containing bioactive substances that can serve as antioxidants. It can be formulated into nanoemulsions to increase bioavailability in the skin. This study aimed to determine the ratio of pine oil and Smix (tween 80 and glycerin) as the optimal base for nanoemulsion based on the highest percent transmittance and to determine the physical characteristics of the S. palustris herb extract nanoemulsion with variations in the amount of extract. Bases of nanoemulsion formula were optimized using a ternary phase diagram and D-Optimal Mixture Design. Nanoemulsion contained three extract concentrations: 0.1; 0.25; and 0.5%, respectively, and nanoemulsion was tested for physical characteristics. The results of this study were a light yellow to light brown, clear, and transparent, with a characteristic weak-strong odor, forming an O/W nanoemulsion. Increasing the concentration of the extract significantly increased the viscosity and decreased the pH and percent transmittance. This study concluded that variations in extract concentration affected the percent transmittance, organoleptic, pH, viscosity, and the optimal ratio of nanoemulsion components was 1% pine oil, 9% Smix, and 90% water.